Adjudicating affirmative action within a normative framework of substantive equality and the Employment Equity Act – an opportunity missed? - Albertyn, Catherine (Juta and Co, 2015)
The development of a constitutionally informed legal standard to test employment equity plans and affirmative action measures will always be troubled in a country that has seen racial classification serve as the basis for oppression and subordination, and now seeks to use it in achieving a ‘non-racial’ democracy. Contestation over how to secure redress, restitution and substantive equality are inevitable. The Barnard judgment demonstrates a common commitment to restitution and transformation, and, indeed, a common outcome. However, between that commitment and the outcome lie important differences in philosophical and legal approaches to equality, to s 9 of the Constitution and s 6 of the Act (and the relationship between them), to the standard of justification for positive measures and to the need for courts to engage substantively with crucial issues in our democracy. In this case-note, after setting out the case history and judgments in some detail, I explore the contrasting ideas of equality that underpin the different approaches to positive measures and discuss which is best suited to our constitutional project. I then suggest how this normative framework can inform the adjudication of employment equity plans and affirmative action measures under the Employment Equity Act. No single judgment in Barnard achieves this.
Keywords: Affirmative action, Substantive Equality, South Africa